Dampak Pemberian Biskuit Daun Katuk terhadap Produksi ASI pada Ibu Menyusui di Wilayah Kerja Puskesmas Kuta Baro Kabupaten Aceh Besar - Erna Erna; Rosalia Putri; Abdi Jihad (Pusat riset dan Inovasi Nasional, 2026)
The production of breast milk is essential for promoting optimal growth and developmental outcomes in infants throughout the first six months of life. Nevertheless, several studies have indicated that some breastfeeding mothers face challenges in producing adequate milk, often influenced by nutritional status, psychological conditions, and environmental support. The katuk plant (Sauropus androgynus), a well-known local herb, has long been recognized for its potential as a natural galactagogue that can stimulate breast milk production. The innovation of processing katuk leaf extract into biscuits offers a more practical, convenient, and potentially acceptable alternative for daily consumption among the community. The present study aimed to examine the impact of katuk leaf biscuits on breast milk production among breastfeeding mothers within the jurisdiction of Kuta Baro Health Center, Aceh Besar District. A pre-experimental design utilizing a one-group pretest–posttest method was implemented, involving 20 breastfeeding mothers who fulfilled the established inclusion criteria. Data collection was carried out through the administration of questionnaires and by measuring breast milk volume using a calibrated measuring cup.The study findings indicated that before the intervention, most participants had relatively low breast milk production, averaging 69.1 ml. After a seven-day intervention, the mean breast milk volume showed a significant increase to 246.5 ml, with a p-value of 0.000 (p < 0.05), the findings indicate that katuk leaf biscuits exert a significant influence on increasing breast milk production. Overall, this study underscores the potential of locally sourced, herbal-based food innovations as an effective and sustainable approach to enhancing breast milk production and supporting the success of exclusive breastfeeding programs.